Organizational Communication Analysis on Employee Performance and Job Satisfaction as Intervening Variables in Three-Star Hotels in Tabanan - I Gusti Gede Ngurah Bimantya Dyananta Arya; Ni Wayan Sitiari; Anak Agung Rai Sita Laksmi (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
The competitive nature of the hotel industry in Bali necessitates the enhancement of competitive advantages, such as Human Resources (HR) development. This study aims to analyze how organizational communication influences employee performance and job satisfaction in Three-Star Hotels in Tabanan Regency. The research involves 55 employees from these hotels and utilizes a survey-based data collection method with questionnaires as instruments. Analytically, Partial Least Squares (PLS) are employed to address hypotheses. Findings indicate that organizational communication positively influences but insignificantly impacts employee performance and job satisfaction. Job satisfaction, however, does not mediate the relationship between organizational communication and employee performance. Limitations include the inability to generalize findings to other industries due to unique characteristics of the hotel industry.